PENGARUH PROMOSI KESEHATAN BINA KELUARGA BALITA (BKB) TERHADAP PERILAKU IBU STIMULASI PERKEMBANGAN ANAK 1000 HPK DI WILAYAH BALAI PENYULUH KB - Susanty, Shantrya Dhelly; Afifa, Rani; Alhamda, Syukra (Universitas Fort De Kock, 2025)
Bina Keluarga Balita (BKB) is a flagship program of BKKBN that aims to increase the knowledge and awareness of mothers and family members about the importance of the physical, mental, and social development process of toddlers, as well as the appropriate and integrated services available for children. A literature review is needed to determine the impact of the Bina Keluarga Balita program on toddler growth and development. The method used in this research is a Systematic Literature Review (SLR) obtained by searching online electronic databases from Google Scholar. Regarding the impact of the Bina Keluarga Balita program on toddler growth and development, 4 journals show that the BKB program can increase parents' knowledge about toddler growth and development, as well as improve their skills in stimulating growth and development. Meanwhile, 1 journal indicates that factors related to child development, such as maternal education level, history of infectious diseases in children, family income, and child nutritional status, need to be addressed in efforts to improve child development, where the BKB program can play a role in providing education to parents.